Assessment of RBD Palm Oil-in-Water Emulsion to Reduce Dust Exposure and Crystalline Silica in Abrasive Blasting - K. Samsudin, Muhammad Ikhwanuddin; Zakaria, Hanis; Abdul Rahman, Muhammad Firdaus; Mohd Azham Azmi; Suhaimi Hassan; Noorul Azreen Azis; Ridwan Abdurrahman (International Journal of Integrated Engineering, 2026)
Abrasive blasting widely used as surface preparation in industrial applications but poses significant occupational health risks due to airborne dust, particularly crystalline silica. This study investigates the effectiveness of Refined, Bleached, and Deodorized (RBD) palm oil-in-water emulsions in reducing inhalable and respirable dust concentrations during abrasive blasting. Using garnet abrasive media (30-60 mesh size) and varying emulsion ratios (95:5, 96:4, 97:3, 98:2, 99:1 and 100:0–water:oil ratio), dust exposure was measured via NIOSH methods; NMAM 0500 for inhalable dust and NMAM 0600 for respirable dust and analyzed using X-Ray Diffraction (XRD). Results show that the 95:5 emulsion ratio achieved up to 86% reduction in inhalable dust and 75% in respirable dust compared to dry blasting. XRD analysis confirmed a significant decrease in crystalline silica content. These findings suggest that RBD palm oil emulsions offer a safer, eco-friendly alternative for industrial blasting operations.